Methodological issues of systematic reviews and meta-analyses in the field of sleep medicine: A meta-epidemiological study - Chang Xu (102022) (2021)
An increasing number of systematic reviews and meta-analyses (SRMAs) have been published in the field of sleep medicine. We evaluated the methodological issues of these SRMAs. A protocol was developed in advance. Three databases were searched from inception to October 2019 for SRMAs published in major academic journals of sleep medicine that assessed healthcare interventions. The AMSTAR 2.0 instrument was used to evaluate the methodological issues and a multivariable regression analysis was conducted to investigate potential measures associated with methodological validity. We identified 163 SRMAs. The median number of missing safeguards of these SRMAs was 7 out of 16 (Interquartile range, IQR: 6–9), and on average, two of these missing safeguards were critical weaknesses. Our regression analysis suggested that SRMAs published in recent years (β = 0.16; 95%CI: 0.08, 0.24; p = 0.002), with the first author from Europe (β = 0.08; 95%CI: 0.02, 0.14; p = 0.013) tend to have higher relative methodological ranks. In conclusion, the methodological validity for current SRMAs in sleep medicine was poor. Further efforts to improve the methodological validity are needed. Other Information Published in: Sleep Medicine Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.smrv.2021.101434